Penyuluhan Optimalisasi Media Sosial untuk Pemasaran Produk UMKM Halal Food di Karanganyar 2023 - Yuni Safitri; Arif Effendi; Rifki Faradi Tarohman (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
The focus of empowerment in community service activities is oriented towards optimizing social media applications in supporting marketing improvement. The focus of empowerment is carried out with the aim of helping stabilize the economic condition of Ploso Village after the Covid-19 pandemic. The following is data on the number of MSMEs in Ploso Village, consisting of 8 snack MSMEs, 3 convection MSMEs, and 1 artisan MSME. Judging from field observations that the condition of assisted subjects is still running their business in a simple and traditional way. Some products produced from the MSME and halal food industries are marketed without giving a brand. Community service activities were attended by approximately 73 participants in each session. In the activity, an explanation was given about the improvement of digital marketing concepts and the use of social media applications as an increase in product marketing. The results of the assistance were carried out optimally. There is also an increase, namely some business actors are starting to learn further to create promotional content through their social media.